Polyclonal Spread of Fosfomycin Resistance among Carbapenemase-Producing Members of the Enterobacterales in the Czech Republic - Mattioni Marchetti, V; Kraftova, L; Finianos, M; Sourenian, T; Hrabak, J; Bitar, I (Microbiology spectrum, 2023)
Fosfomycin (FOS) has been recently reintroduced into clinical practice, but its effectiveness against multidrug-resistant (MDR) Enterobacterales is reduced due to the emergence of FOS resistance. The copresence of carbapenemases and FOS resistance could drastically limit antibiotic treatment. The aims of this study were (i) to investigate fosfomycin susceptibility profiles among carbapenem-resistant Enterobacterales (CRE) in the Czech Republic, (ii) to characterize the genetic environment of fosA genes among the collection, and (iii) to evaluate the presence of amino acid mutations in proteins involved in FOS resistance mechanisms. During the period from December 2018 to February 2022, 293 CRE isolates were collected from different hospitals in the Czech Republic. FOS MICs were assessed by the agar dilution method (ADM), FosA and FosC2 production was detected by the sodium phosphonoformate (PPF) test, and the presence of fosA-like genes was confirmed by PCR. Whole-genome sequencing was conducted with an Illumina NovaSeq 6000 system on selected strains, and the effect of point mutations in the FOS pathway was predicted using PROVEAN. Of these strains, 29% showed low susceptibility to fosfomycin (MIC, ≥16 μg/mL) by ADM. An NDM-producing Escherichia coli sequence type 648 (ST648) strain harbored a fosA10 gene on an IncK plasmid, while a VIM-producing Citrobacter freundii ST673 strain harbored a new fosA7 variant, designated fosA7.9. Analysis of mutations in the FOS pathway revealed several deleterious mutations occurring in GlpT, UhpT, UhpC, CyaA, and GlpR. Results regarding single substitutions in amino acid sequences highlighted a relationship between ST and specific mutations and an enhanced predisposition for certain STs to develop resistance. This study highlights the occurrence of several FOS resistance mechanisms in different clones spreading in the Czech Republic. IMPORTANCE Antimicrobial resistance (AMR) currently represents a concern for human health, and the reintroduction of antibiotics such as fosfomycin into clinical practice can provide further option in treatment of multidrug-resistant (MDR) bacterial infections. However, there is a global increase of fosfomycin-resistant bacteria, reducing its effectiveness. Considering this increase, it is crucial to monitor the spread of fosfomycin resistance in MDR bacteria in clinical settings and to investigate the resistance mechanism at the molecular level. Our study reports a large variety of fosfomycin resistance mechanisms among carbapenemase-producing Enterobacterales (CRE) in the Czech Republic. Our study summarizes the main achievements of our research on the use of molecular technologies, such as next-generation sequencing (NGS), to describe the heterogeneous mechanisms that reduce fosfomycin effectiveness in CRE. The results suggest that a program for widespread monitoring of fosfomycin resistance and epidemiology fosfomycin-resistant organisms can aide timely implementation of countermeasures to maintain the effectiveness of fosfomycin.
Keywords: Microbial Sensitivity Tests; Humans; fosfomycin; drug-resistance bacteria; Enterobacterales; WGS; karbapenemy; mikrobiální testy citlivosti; Escherichia coli; lidé; Fosfomycin; antibakteriální látky; beta-laktamasy; Anti-Bacterial Agents; Carbapenems; Drug Resistance, Bacterial; Czech Republic; beta-Lactamases; bakteriální léková rezistence; Česká republika; carbapenemase producers